Who Will Watch the Watchmen? Czech Documentary After 1989 (a Brief Resume) - Bednařík, Pavel (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
Pavel Bednařík’s paper emphasizes the new era of Czech documentary, focusing on several issues and topics from contemporary Czech docs. Introducing the new era of Czech documentaries since the 1990s, Bednarik’s text depicts the development of its social and political background, including a new upheaval in the auteur documentary approach at FAMU, and leading to inspiration by professor and fi lmmaker Karel Vachek. A case study follows on the successful fi lm alliance between Vít Klusák and Filip Remunda producing the engaged “Czech Journal” for Czech Television within the new production scheme adopted aft er 2013.